Morphometric analysis of the human endoneurial extracellular matrix components during aging - Kundalić, Braca K.; Ugrenović , Slađana Z; Jovanović, Ivan D.; Petrović, Vladimir S.; Petrović, Aleksandar S.; Stojanović, Vesna R.; Antović, Aleksandra R.; Kundalić, Jasen K.; Graovac, Ivana S. (Archives of Biological Sciences, 2021)
Paper description: Aging affects the extracellular matrix (ECM), which is important for normal axonal functioning and supports axonal regeneration. The endoneurial percentages of ECM proteins in human peripheral nerves harvested from 15 cadavers of 3 age groups (25-44; 45-64; 65-86) were examined morphometrically. After the age of 65 there was a significantly higher presence of collagen type IV than in younger groups and a significantly lower expression of collagen type I and laminin. The age-related imbalance of ECM proteins may modify nerve functions in older people by preventing adequate repair and regeneration. Abstract: The aim of this study was to analyze the expression of extracellular matrix (ECM) proteins in human endoneurium during aging. We harvested 15 cadaveric sural nerves, distributed in 3 age groups (I: 25-44, II: 45-64, III: 65-86 years old). Histological sections were stained immunohistochemically for the presence of collagen type I, type IV and laminin, and the ImageJ processing program was used in morphometrical analysis to determine the percentages of these endoneurial proteins. In two younger groups, the endoneurial matrix of the sural nerve was composed from about equal proportions of these proteins, which may be considered a favorable microenvironment for the regeneration of nerve fibers. Linear regression analysis showed a significant increase in endoneurial collagen type IV with age, while collagen type I and laminin significantly decreased during the aging process. In cases older than 65 years, remodeling of the endoneurial matrix was observed to be significantly higher for the presence of collagen type IV, and lower for the expression of collagen type I and laminin. This age-related imbalance of ECM proteins could represent a disadvantageous microenvironment for nerve fiber regeneration in older adults. Our findings contribute to the development of therapeutic approaches for peripheral nerve regeneration.